The use of contact lenses to treat visually symptomatic congenital nystagmus. Issue 2 (23rd January 2004) - Biousse, V; Tusa, R J; Russell, B; Azran, M S; Das, V; Schubert, M S; Ward, M; Newman, N J
Abstract : It has been suggested that contact lens wear improves the visual function of patients with visual loss from congenital nystagmus. In this study, four patients with congenital nystagmus had two evaluations separated by at least one week (one with spectacles, one with contact lenses) including visual acuity, contrast sensitivity, oscillopsia scale, quality of life questionnaire (NEI VFQ-25), and eye movement recording with an infrared tracking system. All patients subjectively preferred contact lenses to spectacles. Their contrast sensitivity and VFQ-25 scores were improved with contact lenses compared with spectacles alone. Several parameters of nystagmus showed no change in two patients, worsening in one patient and improvement in one patient. This suggests that much of the clinical improvement observed in our patients may result from a better optical correction of their refractive error with contact lenses than with spectacles, rather than from a true damping effect of the nystagmus by contact lenses.